Development of an Assay to Determine the Amount of Ca-Fatty Acid Soaps in Feces. (9th September 2020) - Stroebinger, Natascha; Rutherfurd, Shane M; Henare, Sharon J; Moughan, Paul J
Abstract: Background: The quantification of fecal Ca-fatty acid soaps is important to understand how fatty acids behave in the gastrointestinal tract. Objective: As current methods to extract Ca-fatty acid soaps from feces give low recoveries an accurate assay to determine the amount of fatty acid soaps in feces was developed. Method: Ca-fatty acid soaps are determined indirectly after non-soap fatty acid compounds have been extracted from the feces. Synthetic Ca-fatty acid soaps of different chain lengths (C12 –C18 ) and degree of saturation (C18:0 –C18:2 ) were incubated with several solvents to find the solvents that least-solubilize the Ca-fatty acid soaps. A three-step extraction was devised using extractions with hexane, hexane-isopropanol and water either at room temperature or at 60°C, 37°C, or 80°C, respectively. Feces were spiked with free fatty acids, Ca-fatty acid soaps, Na-fatty acid salts, and phospholipids. Results: All of the free fatty acids and phospholipids and almost all of the Na-fatty acid salts were removed and 98% of Ca-lauric acid soap, 99% of Ca-stearic acid soap, and 93% of oleic acid soap were recovered. Conclusions: The method is suitable for determining fatty acids in the form of Ca-fatty acid soaps in feces. Highlights: New method to determine fecal Ca-fatty acid soaps. Consistent and high recovery of fatty acid-soaps.